Low-level air pollution and hospital admissions for cardiac and cerebrovascular diseases in Helsinki. - Pönkä, A (1996)
OBJECTIVES: This study investigated whether low concentrations of ambient air pollutants are associated with hospital admissions for ischemic cardiac and cerebrovascular diseases. METHODS: Associations between daily concentrations of sulfur dioxide, nitric oxide, nitrogen dioxide, ozone, and particulates and daily hospital admissions due to ischemic cardiac and cerebrovascular diseases were studied in Helsinki, Finland, 1987 through 1989. The regression analyses controlled for weather, day of the week, season, long-term trends, and influenza epidemics. RESULTS: Admissions via emergency rooms due to ischemic cardiac diseases (n = 7005) were significantly associated with the prevailing levels of nitric oxide and ozone, and those due to cerebrovascular diseases (n = 3737) were associated with nitrogen dioxide; these levels were only moderate. Long-term transient myocardial ischemic attacks were related to particulates, and short-term ischemic attacks were related to nitrogen dioxide. CONCLUSIONS: Symptoms of ischemic cardiac and cerebrovascular diseases may be provoked by pollutants in concentrations lower than those given as guidelines in many countries and lower than previously shown.